Chronic adaptation of the coracohumeral space and subscapularis tendon in professional baseball pitchers - Schofield, M. R.; Paul, R. W.; Buchheit, P.; Rauch, J.; Thomas, S. J. (Sports Health: A Multidisciplinary Approach, 2025)
Background Pitchers frequently experience anterior shoulder pain, possibly associated with coracohumeral impingement; however, whether the coracohumeral distance (CHD) and/or subscapularis tendon adapt chronically (bilateral difference) due to pitching, and whether clinical measures are associated with CHD and subscapularis tendon organization have not been evaluated in professional pitchers.